The Effect of perceived Benefits, Ease of Use and Security on the Intention to Use the Dana Application - Fahlepi, Muhammad Iqbal; Roslina, Roslina; Husna, Nurul (Pusdikra Publishing, 2023)
In this era of globalization, technology is developing rapidly in all aspects, including the economic aspect. Changes in payment transactions using currency are now starting to be replaced by electronic money. There is a lot of electronic money that is present in the community, one of which is the Dana Application. This is something new among the public so that people are still questioning the benefits, convenience and security of the Dana Application, because when using it transactions are inefficient because when using the Dana Application there are difficulties and transaction security is not guaranteed. The research method used is quantitative, namely a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. In this study using a questionnaire with a Likert scale. The population in this study were Dana Application users and 120 samples were used as a research sample. The results of this study indicate that Perceived Usefulness (X1) has a positive and significant effect on Intention to Use (Y), Ease of Use (X2) has a positive and significant effect on Intention to Use (Y), Safety (X3) has a positive and significant effect on Intention to Use (Y ).